2018
DOI: 10.1177/0959683618771495
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological change and human activity during Yuan–Ming Dynasties in the Loulan area, northwestern China

Abstract: Human activity on arid lands has been related to oases evolution. The ancient Loulan, an important transportation hub of the ancient Silk Road, developed on an ancient oasis on the west bank of the lake Lop Nur in Xinjiang, China. Previous studies and historical documents suggest that the region has experienced dramatic natural environmental and human activity–related changes over time, transitioning from a particularly prosperous oasis to a depopulated zone with harsh environment after about 1500 a BP (before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The last 2000 years in Xinjiang, in arid northwest China, were marked by the flourishing of ancient civilizations, agricultural development, social progress, and increased climatic variability (Li et al, 2018; Mischke et al, 2017; Yang et al, 2009; Zhang et al, 2018). Historical documents and archeological investigations have revealed that the region is climatically sensitive and thus it provides the opportunity to investigate the relationship between human activity and environmental change during a period of high climatic variability (Mischke et al, 2017; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The last 2000 years in Xinjiang, in arid northwest China, were marked by the flourishing of ancient civilizations, agricultural development, social progress, and increased climatic variability (Li et al, 2018; Mischke et al, 2017; Yang et al, 2009; Zhang et al, 2018). Historical documents and archeological investigations have revealed that the region is climatically sensitive and thus it provides the opportunity to investigate the relationship between human activity and environmental change during a period of high climatic variability (Mischke et al, 2017; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The lake is currently eutrophic and considered to be at risk: the level of organic contamination in the water column and in the sediments is higher than that of other lakes surrounded by intensive industrial activity and located in developed countries (Shen et al, 2017). Over the last four decades, the region has experienced extreme hydrological changes in response to climatic warming, which has resulted in increased surface runoff and glacier recession in the surrounding mountains (Li et al, 2018; Wu et al, 2010; Yao et al, 2018). In addition, the area of Bosten Lake has decreased sharply over the last decade (2000–2016) (Tan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations